Using java (Que, 1996)
The book uses Java which is suitable as a vehicle in teaching object-oriented programming for beginners. Other features include: incremental program development; JDK (Java Development Kit) 1.1-compatible; and all programming tasks, examples, exercises and codes are presented in Java